2008
DOI: 10.1111/j.1471-0528.2008.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on cognitive functions in climacteric syndrome: a randomised control study

Abstract: Objective To assess the efficacy of an integrated approach of yoga therapy (IAYT) on cognitive abilities in climacteric syndrome.Design A randomised control study wherein the participants were divided into experimental and control groups.Settings Fourteen centres of Swami Vivekananda Yoga Research Foundation, Bangalore, India.Sample One hundred and eight perimenopausal women between 40 and 55 years with follicle-stimulating hormone level equal to or greater than 15 miu/ml. One hundred and twenty perimenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…Previous studies have shown that the practice of yoga improves cognitive function, [11][12][13][14][15] although some studies have found contradicting results. 16,17 Given these conflicting results, and the lack of research about the effect of yoga on PMS, the primary aims of this study were to evaluate the effect of yoga exercise on women with PMS and to determine the immediate change of attention performance after yoga classes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the practice of yoga improves cognitive function, [11][12][13][14][15] although some studies have found contradicting results. 16,17 Given these conflicting results, and the lack of research about the effect of yoga on PMS, the primary aims of this study were to evaluate the effect of yoga exercise on women with PMS and to determine the immediate change of attention performance after yoga classes.…”
Section: Introductionmentioning
confidence: 99%
“…1-4 However, randomized controlled trials (RCTs) failed to show significant improvements in self-reported sleep with yoga compared to gentle exercise, 5 moderate-intensity walking, 6 or usual care. 6 Only one yoga RCT of midlife women required participants to meet clinical diagnostic criteria for insomnia and reported significant improvement in insomnia symptoms versus usual care.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga and exercise have been suggested as useful nonpharmacologic treatments for midlife women experiencing sleep disturbance, but evidence regarding efficacy remains mixed and inconclusive. Several studies of yoga interventions for 8 to 16 w duration in women during and after menopause [1][2][3][4][5][6] showed statistically significant within-group improvements in self-reported sleep outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 months of yoga practicing, physical fitness of older adults was significantly improved. Previous findings supported yoga as a measure to improving cognitive functions (Chattha, Nagarathna, Padmalatha, & R, 2009), subjective well-being (K. Sharma, 2008), different aspects of mental health (Gururaja, Harano, Toyotake, & Kobayashi, 2011;, cardiovascular system (Bharshankar, Bharshankar, Deshpande, Kaore, & Gosavi, 2003), physical and mental health (Buessing, Michalsen, Khalsa, Telles, & Sherman, 2012). Researchers also revealed that yoga has benefits for aging population.…”
Section: Discussionmentioning
confidence: 86%